Edulcorantes artificiales en la Industria Alimentaria - Reyes Asto, Milagros Amelia (2017)
Artificial sweeteners, also known as sugar substitutes, are substances that are used in the place of the beverage to sweeten beverages and foods, and much sweeter than sugar. In addition, the information provided to the consumer on sweeteners is contradictory since it depends on the motive and the investment of the industry or the agency that provides the information. All sweeteners have the characteristic of having a sweet taste but their sweetness varies in each case, also called relative sweetness, of a defined substance is defined as the ratio between the concentration of a given solution of sucrose in the water and the concentration of the Solution of sweetener, of equivalent intensity in water. The sweeteners currently available in the Peruvian market are aspartame, saccharin and sucralose. Aspartame is a molecule that contains the drift of two amino acids: aspartic acid and phenylalanine, and has a sweetening power of 180 to 200 times more than sucrose and one of the main concerns now is the level of damage and toxicity that Can be generated methanol released by aspartame; Saccharin is an inorganic compound, is approx. 100 to 300 times sweeter than sucrose and has a bitter-metallic taste at high concentrations and sucralose is 600 times sweeter than sucrose. Recent studies that artificial sweeteners especially in beverages can be helpful in reducing energy consumption such as body weight and lowering the risk of type II diabetes and cardiovascular disease, when compared to the intake of sugars. But to be able to affirm it, it requires its confirmation of a long term in the studies designed for this purpose